Conventional vs virtual autopsy with postmortem MRI in phenotypic characterization of stillbirths and fetal malformations. (7th February 2018) - Shruthi, M.; Gupta, N.; Jana, M.; Mridha, A. R.; Kumar, A.; Agarwal, R.; Sharma, R.; Deka, D.; Gupta, A. K.; Kabra, M.
ABSTRACT: Objective: To compare virtual autopsy using postmortem magnetic resonance imaging (MRI) with conventional autopsy with respect to phenotypic characterization of stillbirths and malformed fetuses, and acceptability to parents. Methods: This was a prospective diagnostic evaluation study, conducted from June 2013 to June 2015, including stillbirths and pregnancies terminated owing to fetal malformation at ≥ 20 weeks' gestation, for which parental consent to both conventional autopsy and postmortem MRI was obtained. Cases of maternal and obstetric cause of fetal demise were excluded. Whole‐body postmortem MRI (at 1.5 T) was performed prior to conventional autopsy. Taking conventional autopsy as the diagnostic gold standard, postmortem MRI findings alone, or in conjunction with other minimally invasive prenatal and postmortem investigations, were assessed and compared for diagnostic accuracy. Results: Parental consent for both conventional autopsy and postmortem MRI was obtained in 52 cases of which 43 were included in the analysis. In 35 (81.4%) cases, the final diagnosis based on virtual autopsy with postmortem MRI was in agreement with that of conventional autopsy. With conventional autopsy as the reference standard, sensitivity, specificity, positive and negative predictive values of postmortem MRI were, respectively: 77.7%, 99.8%, 97.4% and 98.0% for whole‐body assessment; 93.1%, 99.0%, 87.1% and 99.5% for the nervous system; 61.0%, 100.0%, 100.0% and 96.7% for the cardiovascular system; 91.1%, 100.0%, 100.0% and 98.0% for the pulmonary system; 80.6%, 99.8%, 96.7% and 98.7% for the abdomen; 96.2%, 99.7%, 96.2% and 99.7% for the renal system; and 66.7%, 100.0%, 100.0% and 97.2% for the musculoskeletal system. Virtual autopsy was acceptable to 96.8% of families as compared with conventional autopsy to 82.5%. Conclusions: Virtual autopsy using postmortem MRI and other minimally invasive investigations can be an acceptable alternative to conventional autopsy when the latter is refused by the parents. Postmortem MRI is more acceptable to parents and can provide additional diagnostic information on brain and spinal cord malformations. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.